We love painting : The Contemporary American Art from Misumi Collection. - Tokyo Metropolitan Art Museum, Tokyo; Hiromoto, Nobuyuki; Shioda, Junichi; Taguchi, Hiroshi (Misumi Corporation,., 2002)
Appel, Kevin ; Baldessari, John ; Barth, Uta ; Basquiat, Jean-Michel ; Bevilacqua, Michael ; Bogin, Greg ; Burton, Richmond ; Cain, Peter ; Calame, Ingrid ; Crewdson, Gregory ; Davie, Karin ; de Goede, Leo ; de Kooning, Willem ; Diebenkorn, Richard ; Dine, Jim ; Dunham, Carroll ; Halley, Peter ; Haring, Keith ; Hollingsworth, Dennis ; Johns, Jasper ; Judd, Donald ; Kelly, Ellsworth ; Lasker, Jonathan ; Lethbridge, Julian ; LeWitt, Sol ; Lichtenstein, Roy ; Motherwell, Robert ; Muniz, Vik ; Parrino, Steven ; Prince, Richard ; Rauschenberg, Robert ; Reed, David ; Reeves, Jennifer ; Rosenquist, James ; Ruscha, Edward ; Salle, David ; Shotz, Alyson ; Smith, Kiki ; Stella, Frank ; Do-Ho, Suh ; Taaffe, Philip ; Warhol, Andy ; Wool, Christopher
biog. & bibliog. p. 208-229
English-Japanese
We love painting : the Contemporary American Art from Misumi Collection, Museum of Contemporary Art, Tokyo, December 21, 2002 - March 23
kunstcatalogus
Keywords: U.S.A.